(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2022)
Geotechnical engineering work becomes challenging when the sub-grade is revealed to be silt or silty clay soil. Clay-rich soils inflate when the moisture level in the soil is allowed to rise. Because of their geologic nature, textural qualities, and climatic conditions, most soils in the south of Iraq have a well-known diversity of formations among the world’s soils. Because the soil particles are surrounded by molecules of chlorides, sulfates, or other species of salts, which act as link agents to fill in the gaps in the dry condition, most soils in the Marshes area of Thi-Qar Governorate can be classed as saline soils. The sort of salt in such soil determines how it is disposed of. Chloride salts, for example, are more common and more readily dissolve in water The goal of this research is to improve the geotechnical qualities of soil by using Portland cement and different chloride salt compounds. Salt concentrations of 2%, 4%, 8%, and 10% were applied to the soil to see how they affected compaction characteristics and consistency limits. According to the findings of the study, increasing the amount of each chloride component raised the maximum dry density while decreasing the optimum moisture level. As salt content grows, the liquid limit, plastic limit, and plasticity index all drop.